Antioxidant Levels, Chlorophyll, Carotenoids, and Antibacterial Activities of Caulerpa lentillifera From The North Coast of Java and Bali - Elyanti, Ratih Nurfaizi; Alamsjah, Moch. Amin; Sulmartiwi, Laksmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of caulerpa habitat location on the content of active compounds and their activities as antibacterial. This research is experimental and data analysis with ANOVA. Samples come from three different locations of CBL, CBB, and CL as well as two different solvents, ethanol and n-hexane. According to research, the highest antioxidant activity produced by n-hexane CBL is 73.48%. The highest value of phenol gives n-hexane CBB at 292,867 mg/mL. The highest total flavonoids are 11.91 mg/ml produced by CBB ethanol. The total chlorophyll is between 0.25–0.87 mg/mL, while the total carotenoid is between 1.40–4.11 µ mol/L. The clear zone is formed in only 2 samples with S-test bacteria. It has 0.5 mm aureus n-hexane CBB and 1.5 mm n-hexane CL. This zone is clearly classified as very small, this can be due to the small content of the extract in the test sample. Active compounds found under the GCMS test are alkanes, alkenes, alcohols, and other fatty acids. These active compounds are a group of potentially antioxidant and antibacterial agents. It can be inferred that habitat location affects active compounds and CBB has greater potential as a source of natural materials than other samples.